SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL DARI CANGKANG BUAH JARAK PAGAR - Dede Hermawan, Ana Agustina, Ono Suparno, Ika Amalia Kartika (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
The jatropha shell is a by-product from jatropha oil production. It is a potential cellulosic material for particleboard because of its high fiber content (40%). The purposes of this study were to determine the physical and mechanical properties of the particleboard produced from the jatropha shell, and to investigate the effect of the adhesive agent concentration on the particleboard quality. The adhesive agents used were phenol formaldehyde (12, 14 and 16%) and urea formaldehyde (10, 12 and 14%). The physical and mechanical properties of the particleboard were examined using JIS A 5908-2003. The results showed that the phenol formaldehyde as adhesive agent could improve the dimensional stability and mechanical properties of the particleboard. An increase of adhesive agent concentration increased modulus of elasticity, modulus of rupture, internal bond and wood screw holding power of particle board, and decreased water content, water absorption and thickness swelling of particleboard. Most of the physical and mechanical properties of the jatropha shell particleboard obtained in this study did not meet JIS A 5908-2003, and was not appropriate to be used as a construction material. Keywords: Jatropha shell, particleboard, phenol formaldehyde, urea formaldehyde